2022
DOI: 10.1002/adfm.202201498
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering of a Ceramic Electrolyte by Ta2O5 Nanofilms for Ultrastable Lithium Metal Batteries

Abstract: Solid‐state batteries (SSBs) are promising for next‐generation energy storage with advantages in both energy density and safety, but are challenged by the poor solid‐to‐solid contact between solid‐state electrolytes (SSEs) and electrodes, particularly the lithium anode. Herein, a facile coordination‐assisted deposition process is employed to build artificial Ta2O5 nanofilms on SSEs, which is lithiophilic and has high stability against metallic lithium, thereby ensuring an intimate and stable interface between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Moreover, more in‐depth understanding and exploration should be continued to pursue the long‐term development of SSEs. [ 28,29 ]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, more in‐depth understanding and exploration should be continued to pursue the long‐term development of SSEs. [ 28,29 ]…”
Section: Introductionmentioning
confidence: 99%
“…20 Wan et al applied coordination-assisted deposition to improve interface stability with the Ta 2 O 5 layer. 21 Guo et al adopted physical vapor deposition to deposit SnO 2 onto the surface of LLZO to alloy with Li metal. 22 Nevertheless, these methods mostly rely on expensive and sophisticated equipment, which is not capable of large-scale application.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al used atomic layer deposition to fabricate an Al 2 O 3 layer and decreased the interface resistance of Li/LLZO to 1 Ω cm 2 at 25 °C . Wan et al applied coordination-assisted deposition to improve interface stability with the Ta 2 O 5 layer . Guo et al adopted physical vapor deposition to deposit SnO 2 onto the surface of LLZO to alloy with Li metal .…”
Section: Introductionmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) have been widely used on a large variety of occasions including portable devices and electric vehicles. However, the continuous pursuit of the energy density of LIBs meanwhile raises serious concerns on the issues of safety and reliability of the LIB devices. Although liquid electrolytes endow the LIBs with extraordinary capability for high Li + transportation, the flammable nature of the organic electrolytes makes the LIBs unstable due to the inevitable side reactions with high energy electrodes during the continuous charge/discharge processes. Accordingly, solid-state electrolytes (SSEs) are considered as attractive alternatives for those liquid ones due to their obvious advantage when the stability issue is considered. Taking a typical SSB, namely, the garnet-typed Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 (LLZT), as an example, these SSEs can show an electrochemical window of 0–6 V, which is much higher than their liquid counterpart, and maintain a high Li + conductivity of ∼10 –3 S cm –1 at room temperature. Meanwhile, this ceramic electrolyte is also known for its excellent mechanical stability , and electrochemical stability against Li metal, , which makes it possible to integrate the use of metallic Li as the anode to achieve both high energy density and high safety for the prepared batteries, accordingly making the SSBs promising systems for next-generation energy storage applications. , …”
Section: Introductionmentioning
confidence: 99%
“…12−14 Meanwhile, this ceramic electrolyte is also known for its excellent mechanical stability 1,15 and electrochemical stability against Li metal, 16,17 which makes it possible to integrate the use of metallic Li as the anode to achieve both high energy density and high safety for the prepared batteries, accordingly making the SSBs promising systems for next-generation energy storage applications. 18,19 Despite the obvious advantage of the use of SSEs, the contact between SSEs and Li metal becomes a concern for their practical application. 16,20 As for the LLZT pellet, it is widely reported that impurities such as Li 2 CO 3 and LiOH can be easily formed on the LLZT particle surface during the preparation and storage process.…”
Section: Introductionmentioning
confidence: 99%